Facsimiles of Medieval Icelandic Manuscripts - Colceriu, Natalie Julia 1981- (2008)
Icelandic manuscripts, particularly the medieval manuscripts housed at the Árni Magnússon Institutes and the history of their duplication through facsimile-making processes will be the focus of this paper. A vast amount of research had to be undertaken, collecting various sources in English and Icelandic, to compile the history of facsimile productions. To my knowledge, no compilation of the history of medieval Icelandic facsimile production has written before, especially not to this breadth and depth or in English. The first chapter will provide an overview of the history of facsimile reproduction divided into sections according to facsimile medium. The definition of ‘facsimile’ means a copy or reproduction of an original and comes from the Latin fac simile translated as “make similar.” For our purposes it will be specifically a copy of a manuscript produced photographically. Facsimile creators strive to replicate the manuscript as accurately as possible so that scholars can rely upon the facsimile. In Iceland and in Denmark, several graphic techniques have created facsimiles—copperplate press, lithography, and various photographic processes from traditional to digital. These processes, their histories and results, will be chronicled regarding Icelandic manuscripts. The second chapter isolates the primary reason for facsimile creation, which is access. What were and are the incentives and goals of the manuscript institutions? How accessible are the original manuscripts? The answers to these questions further illustrate the importance of access and facsimiles. Finally, the third chapter highlights issues surrounding the different facsimiles formats. First the benefits of using the original manuscript are listed as a means of showing some of the disadvantages associated with the other formats. Then issues surrounding print facsimiles will be discussed. Next is the section on issues surrounding photographs and microfilm, which is followed by the final section, issues surrounding the digital format.